PENERAPAN STRATEGI BELAJAR INVESTIGASI KELOMPOK UNTUK MENINGKATKAN MOTIVASI BELAJAR FISIKA SISWA KELAS X1 SMAN I TAMBANG KAMPAR - M. Nasir; Harnawati Harnawati; Zuhdi Ma’aruf (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2007)
The purpose of this research was to find improvement in the student physics learning motivation in teaching physics by applying group investigation by the first-year student SMA N 1 Tambang Kampar in the academic year 2005/2006. Improvement learning motivation is seen 15 learning motivation indicators. The subject of the research is the student X1 class of SMA N 1 Kampar the sample taken was 42 students. The research instrument used for collecting data in this research is questioner first motivation and questioner end motivation. The student motivation data analysis by descriptive analysis and differential analysis. The descriptive analysis showed that : (1) The improve student learning motivation as the topic rectilinear motion kinematic by applying group investigation implementation is categorized high and (2) Differential analysis showed that implementation group investigation learning strategy in the learning process can improve student learning motivation X1 class of SMA N 1 Tambang Kampar with improving 8,8%.